Analisis Akad Ijarah Muntahiah Bi At Tamlik Dalam Praktik Perbankan Syariah - Nilatus Salamah; Miftahur rahman (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
IMBT is a form of multi-contract product. At the beginning of the contract agreement used by both parties is an ijarah agreement so that there is a transfer of the right to use the benefits from the lessor (Mu'jir/muajir) to the lessee (Musta'jir) accompanied by the transfer of property rights from mu'jir to muajir on the basis of promise. The ijrah contract with ownership at the end is a contract that has been recognized by the Indonesian Ulema Council through the DSN. In Islamic banking, the application of ijarah and IMBT products, the bank works as an investor/provider of funds and promises. This paper aims to find out how IMBT is in Islamic Banking. This study uses a type of library research (library research). Data collection techniques were carried out by means of documentation studies and triangulation. The data analysis technique was carried out by content analysis using a qualitative study with a conceptual realm. The results of the study show that if there is a dispute between the parties, the settlement guideline is an